Development of Audio Visual Media Based on Sparkol Videoscribe in Thematic Learning in 4th Grade Elementary School - Khasanah, Uswatun; Rahma Pratiwi, Emy Yunita (IJPSE : Indonesian Journal of Primary Science Education, 2021)
The role of learning media in the learning process is an integral part that cannot be separated from the world of education. The important role of the media is very influential on the learning outcomes of students in the classroom. Through interviews and observations with class teachers, it was found that there were problems that existed at SDIT Darul Falah, one of which was the use of media in the classroom infrequently. From the results of these observations and interviews, researchers had the opportunity to develop an audiovisual media using a sparkol videoscribe-based whiteboard animation. This study aims to develop learning media and determine the development of the R2D2 model which has been modified by the researcher according to the needs with the define, and design and development stages. The data analysis technique to assess validity was calculated by finding the final score and its relevance to the Likert scale, while the analysis of student test data was calculated by looking for DSI (individual absorption), RK (class average), and KBK (classical mastery learning). Students are said to be able to absorb learning and learning is said to be successful if the final results of DSI and RK are above 68 (KKM SDIT Darul Falah). Based on research that has been done, the results of this development product are published in 3 versions, namely by web, CD (compact disk), and also on youtube. The results of field trials through the use of sparkol videoscribe-based media can be said to be valid with an overall average of 89.5. Then the learning outcomes of students with an average of 77.5, the number of students completed with a percentage of 88.9%.